2019
DOI: 10.3390/ijms20143550
|View full text |Cite
|
Sign up to set email alerts
|

Complement System in Cutaneous Squamous Cell Carcinoma

Abstract: Epidermal keratinocyte-derived cutaneous squamous cell carcinoma (cSCC) is the most common metastatic skin cancer with high mortality rates in the advanced stage. Chronic inflammation is a recognized risk factor for cSCC progression and the complement system, as a part of innate immunity, belongs to the microenvironment of tumors. The complement system is a double-edged sword in cancer, since complement activation is involved in anti-tumor cytotoxicity and immune responses, but it also promotes cancer progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 115 publications
(232 reference statements)
0
50
0
Order By: Relevance
“…The balance between cancer and immune system is a milestone for the malignant cell development and this event is considered critical for the SCC development [ 98 , 99 ]. Many studies have suggested that disruption of immune-editing phases is required for SCC, while both UV exposure and viral infections cooperate for the impairment of immune system response.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
“…The balance between cancer and immune system is a milestone for the malignant cell development and this event is considered critical for the SCC development [ 98 , 99 ]. Many studies have suggested that disruption of immune-editing phases is required for SCC, while both UV exposure and viral infections cooperate for the impairment of immune system response.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
“…It is also worth mentioning that the inhibitors of complement signals act in a relatively systematic manner to the in-depth investigation of complement signaling in non-tumor immune-related diseases, such as organ transplantation. There are at least 30 inhibitors or neutralizing antibodies targeting 14 complement signaling molecules that are currently undergoing clinical trials ( Riihila et al, 2019 ), as represented by eculizumab, an inhibitor of C5, recently has been reported to effectively re-establishes regulation of the innate immune complement system to substantially reduce the pathophysiological manifestations of human CHAPLE disease ( Ozen et al, 2021 ) and IPH5401, a C5aR neutralizing antibody was combined with Durvalumab to treat Patients with advanced solid tumors (STELLAR-001) (Clinical trail, NCT number: 03665129). All of the above descripted suggest that in numerous tumors, including malignant gliomas, targeting complement signaling pathways may become a new, effective, and easy treatment strategy in the future.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…[ 37,40 ] Similar driver gene mutations have been identified even in chronically sun‐exposed normal epidermal keratinocytes in chronically sun‐exposed normal looking skin indicating that other alterations, for example in non‐coding RNAs and in the microenvironment of premalignant lesions, are required in the keratinocyte carcinogenesis towards invasive cSCC. [ 15,41,42 ]…”
Section: Keratinocyte Carcinomasmentioning
confidence: 99%